Mekanimse Tata Kelola yang Ada Di Perusahaandan Pengarunya TerhadapKinerja Perusahaan yang Mmemiliki Struktur Kepemilikan yang Berbeda dalam Keadaan Ekonomi yang Tidak Menentu - Astuti, Neni (PERMANA, 2013)
This article examines the relationships among ownership structure, firm risk, economic uncertainty, and governance mechanisms. Governance mechanisms, play the role of reducing opportunistic behavior by either shareholders with controlling interest in the company or manajemen in a company with dispersed shareholding, to undertake financing, investment decisions that benefit their interests, while adversely affecting those of other shareholders, especially those with minority interests (in the case of controlling shareholders); and all stakeholders, including shareholders,creditors among others (agency costs). Under conditions of economic uncertainty, given similar governance mechanisms, firms with controlling interests that takes the form of families or family groups, are shown to be more vulnerable to opportunistic behavior than firms with other forms of ownership structure. This happens to be the case even if such firms are listed on capital markets, since the proportion of shares listed is more often than not, small, which is intended to ensure that though such firms are obliged to abide by information disclosure requirements at a regular basic which is one form of corporate governance, those with controlling retain their clout in determining key financing, investment, and even dividend policies. To that end, the short paper recommends regulatory authorities to impose more stringent corporate governance requirements during conditions of economic adversity for firms that have controlling interests that take the form of families or family groups, private interest groups driven entirely by profit motives and even state owned enterprises. Key Words: Economic uncertainty,capital structure, corporate governance, incentive mechanisms